Light-driven oscillations of entangled nematic colloidal chains. - Gomilšek, M; Seč, D; Skarabot, M; Ravnik, M; Zumer, S; Muševič, I (Springer New York LLC, 2010)
Laser tweezers have been used to drive the oscillations of a chain of entangled colloidal particles in the nematic liquid crystal 5CB. The amplitude and phase of light-driven oscillations have been determined for the motion of individual colloidal particles. The collective motion of 4.8μm silica particles is highly damped for a driving frequency above 0.5Hz. The results were compared to an effective bead-spring model, where the motion of elastically coupled particles is hindered by viscous damping and hydrodynamic coupling. Qualitative agreement between theory and experiment was obtained.